METODE DETEKSI FASA PADA SALURAN LISTRIK TEGANGAN RENDAH DENGAN Esp32 DAN KOMUNIKASI LoRa - Darmana, Tasdik; Putra, Rizki Pratama; Sitorus, Meyhart Torsna Bangkit; Multi, Abdul; Ariman (AGUSPATI Research Institute, 2022)
Load balancing on a low-voltage distribution sistem by adjusting the phase of the new load to be installed requires information on the type of line phase that will be connected to the load. In this research, a phase reading method is proposed using Esp32 with LoRa communication. The purpose of this research is to make a method of reading phase with independent and reliable communication. The phase reading method is carried out by calculating the time difference between the periodic zero values of a phase and then comparing it with other phases to determine the type of phase based on its similarity. With this principle the effect of harmoniks can be reduced where the harmoniks do not affect the time of the zero value of the periodic sinusional wave. Based on the results of the review conducted, this method is better than the conventional method using an electronic mosfet circuit or logic gate where the reference signal cannot be adjusted and the fabrication process is for high-cost commercialization